Pengembangan Sistem Informasi Pendaftaran Seminar Kerja Praktek Program Studi Sistem Komputer Universitas Surakarta Berbasis CodeIgniter 3 - Dwi Prihtapambudi; Budi Nugroho; Cicilia Puji Rahayu (Politeknosains, 2019)
Based on the results of practical work in the administrative office of the Computer System Study Program at the Faculty of Electrical and Informatics Engineering, University of Surakarta, the author has made a web-based practical work seminar registration information system using the PHP programming language assisted with framework codeigniter 3. The system is still intended for administrative staff and have not been given registration facilities for students online, in connection with this case students who want to register for practical work seminars still have to come to program administration. Based on these problems, the author is motivated to develop a practical work seminar registration information system by adding facilities so students can register for practical work seminars online. Making this information system requires MySQL and PHPMyAdmin as a system database. For system design, the author uses CSS and bootstrap to make the display of information systems interesting, and for the main programming language the author uses the PHP programming language that is assisted with framework codeigniter 3. The stages in making this information system, begins with analyzing the system that is running and analyzing system requirements. The second stage is done designing the system database. The third stage is to design a system display design. The fourth stage lists the programs and compiles the program. The fifth stage is testing the system, from the results of the test it can be concluded that the practical work seminar registration information system is going well. The last step is to install the program into the hosting server. The addition of registration facilities for students facilitates the online student registration process. The registration proof output and student registration report are also more effective and efficient.